CXCL10 May Be Responsible for Susceptibility to Pulmonary Embolism in COVID-19 Patients - Liu Y; Si D; Bai P; Zhu L; Zhang L; Chen Q; Qi Y (Dove Medical Press, 2023)
Yingli Liu,1 Dan Si,2 Pingping Bai,3 Li Zhu,4 Lili Zhang,1 Qi Chen,5 Yong Qi6 1Department of Pulmonary and Critical Care Medicine, Zhengzhou University People's Hospital, Henan Provincial People's Hospital, Zhengzhou, Henan, 450003, People's Republic of China; 2Department of Pulmonary and Critical Care Medicine, Central China Fuwai Hospital, Central China Fuwai Hospital of Zhengzhou University, Zhengzhou, Henan, 451464, People's Republic of China; 3Department of Health Management, Henan Provincial People's Hospital, Zhengzhou University People's Hospital, Zhengzhou, Henan, 450003, People's Republic of China; 4Department of Pulmonary and Critical Care Medicine, Zhengzhou University People's Hospital, Henan Provincial People's Hospital, Academy of Medical Science, Zhengzhou University, Zhengzhou, Henan, 450003, People's Republic of China; 5Department of Pulmonary and Critical Care Medicine, Henan University People's Hospital, Henan Provincial People's Hospital, Zhengzhou, Henan, 450003, People's Republic of China; 6Department of Pulmonary and Critical Care Medicine, Zhengzhou University People's Hospital, Henan Provincial People's Hospital, Henan University People's Hospital, Zhengzhou, Henan, 450003, People's Republic of ChinaCorrespondence: Yong Qi, Department of Pulmonary and Critical Care Medicine, Zhengzhou University People's Hospital, Henan Provincial People's Hospital, Henan University People's Hospital, No. 7 Weiwu Road, Jinshui District, Zhengzhou, 450003, People's Republic of China, Tel +8615890110258, Email qiyong@zzu.edu.cnBackground: Although the potential of coronavirus disease 2019 (COVID-19) patients to develop pulmonary embolism (PE) is widely recognized, the underlying mechanism has not been completely elucidated. This study aimed to identify genes common to COVID-19 and PE to reveal the underlying pathogenesis of susceptibility to PE in COVID-19 patients.Methods: COVID-19 genes were obtained from the GEO database and the OMIM, CTD, GeneCards, and DisGeNET databases; PE genes were obtained from the OMIM, CTD, GeneCards, and DisGeNET databases. We overlapped the genes of COVID-19 and PE to obtain common genes for additional analysis, including functional enrichment, protein-protein interaction, and immune infiltration analysis. Hub genes were identified using cytoHubba, a plugin of Cytoscape, and validated using the independent datasets GSE167000 and GSE13535. The genes validated by the above datasets were further validated in clinical samples.Results: We obtained 36 genes shared by PE and COVID-19. Functional enrichment and immune infiltration analyses revealed the involvement of cytokines and immune activation. Five genes (CCL2, CXCL10, ALB, EGF, and MKI67) were identified as hub genes common to COVID-19 and PE. CXCL10 was validated in both independent datasets (GSE167000 and GSE13535). Serum levels of CXCL10 in the COVID-19 group and the COVID-19 combined with PE group were significantly higher than those in the healthy control group (P< 0.001). In addition, there were significant differences between the COVID-19 group and the COVID-19 combined with PE group (P< 0.01).Conclusion: Our study reveals common genes shared by PE and COVID-19 and identifies CXCL10 as a possible cause of susceptibility to PE in COVID-19 patients.Graphical Abstract: Keywords: pulmonary embolism, coronavirus disease 2019, bioinformatics, CXCL10